A UML extension for web design model for interaction process and user interface - Mubin, Siti Azreena (2017)
Nowadays, the process of designing web application has become a challenge for many individuals. The designs should incorporate conceptual domain, interaction processes, navigation structures, and abstract presentation design. Unfortunately, many practitioners believe that most of the web design models have been developed in an ad hoc manner and there is less focus on the interaction processes. Thus, it can lead to a web design that is full of information, confusing navigation, and poor presentation layout. Hence, as a solution to the mentioned problem, this study proposes a web design model called UML Extension Web Design Method (UEWDM) that comprises the conceptual design model, navigational model and user interface model which utilises Unified Modeling Language (UML) profile as the design modeling for the interaction processes and user interface. The extension stereotypes of UML design modeling is also proposed to complement the design modeling in the respective design stages. In order to verify and validate UEWDM, a case study has been developed and feedback from web experts are gathered as to ensure UEWDM is aligned with the developed case study. The results indicate positive feedback from the web experts as all web experts involved in this study agreed with the proposed design model. In conclusion, UEWDM provides a web design model with enough expressivity in modeling interaction processes in web applications. In other words, it could assist web designers and developers in designing web applications that consist of interaction processes and user interface.